2021
DOI: 10.3389/fpsyg.2021.713665
|View full text |Cite
|
Sign up to set email alerts
|

Processing Mandarin Tone 3 Sandhi at the Morphosyntactic Interface: Reduplication and Lexical Compounds

Abstract: Mandarin tone 3 sandhi is a phonological alternation in which the initial tone 3 (i.e., low tone) syllable changes to a tone 2 (i.e., rising tone) when followed by another tone 3. The present study used a cross-modal syllable-morpheme matching experiment to examine how native speakers process the sandhi sequences derived from verb reduplication and compounding, respectively. Embedded in a visually-presented sentential context, a disyllabic sequence containing a sandhi target was displayed simultaneously with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…For studies on grammatical category, two new perspectives are available, namely, morpho-syntactical and constructional. Morpho-syntactically, some scholars hold that the reduplicant is an affix (Sui, 2018;Gao et al, 2021). Gao et al (2021) conducted empirical studies on Mandarin tone sandhi of VV reduplication and lexical compounds and found out that for VV reduplication, only the monomorphemic verb base was accessed in the mental lexicon and "the second constituent likely serves as an affix", therefore, unlike lexical compounds, VV reduplication "is not stored as a lexical entry" (Gao et al, 2021: p. 16).…”
Section: A Brief Review Of Studies On Grammatical Category and Gramma...mentioning
confidence: 99%
See 2 more Smart Citations
“…For studies on grammatical category, two new perspectives are available, namely, morpho-syntactical and constructional. Morpho-syntactically, some scholars hold that the reduplicant is an affix (Sui, 2018;Gao et al, 2021). Gao et al (2021) conducted empirical studies on Mandarin tone sandhi of VV reduplication and lexical compounds and found out that for VV reduplication, only the monomorphemic verb base was accessed in the mental lexicon and "the second constituent likely serves as an affix", therefore, unlike lexical compounds, VV reduplication "is not stored as a lexical entry" (Gao et al, 2021: p. 16).…”
Section: A Brief Review Of Studies On Grammatical Category and Gramma...mentioning
confidence: 99%
“…Morpho-syntactically, some scholars hold that the reduplicant is an affix (Sui, 2018;Gao et al, 2021). Gao et al (2021) conducted empirical studies on Mandarin tone sandhi of VV reduplication and lexical compounds and found out that for VV reduplication, only the monomorphemic verb base was accessed in the mental lexicon and "the second constituent likely serves as an affix", therefore, unlike lexical compounds, VV reduplication "is not stored as a lexical entry" (Gao et al, 2021: p. 16). Chen & Wu (2023) seem to agree that the reduplicant is an affix and argues that VV reduplication is a post-syntax PF (phonetic form) operation caused by lowering of de-limitative aspect head which induced the phonetic copying of the verb.…”
Section: A Brief Review Of Studies On Grammatical Category and Gramma...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous studies [12][13][14] [15] reviewed various rules in tone sandhi in Chinese languages in terms of the directionality sandhi system. In the realm of tone sandhi, one of the most interesting phenomena is the Tone 3 sandhi (T3).…”
Section: Background Of Studymentioning
confidence: 99%
“…Even regarding tone sandhi, some recent research suggests that different processing mechanisms may be involved in the tone sandhi processing in other Chinese dialects (Chang et al, 2019;Chien et al, 2017;Yan et al, 2020Yan et al, , 2021. Moreover, the application of tone sandhi is also subject to other factors such as morphosyntactic structure and prosodic structure (Chen, 2000), and recent research suggests that the processing of disyllabic Mandarin T3 sandhi words with different morphological structures (e.g., lexical compounds vs. reduplication) may also differ (Gao et al, 2021). Future research should elucidate the processing of different types of phonological alternations and the interaction with other high-level linguistic factors including syntax and semantics and delineate the conditions or contexts that will affect the processing mechanisms.…”
Section: Implications For Other Issuesmentioning
confidence: 99%